The Clinical Impact of Vascular Endothelial Growth Factor/Receptor (VEGF/R) Inhibitors on Voice - Ng, Christina Hui Lee; Damrose, Edward J. (Case Reports in Otolaryngology, 2023)
Background. Vascular endothelial growth factor/receptor (VEGF/R) inhibitors are used in chemotherapy protocols to limit tumor angiogenesis. Recent evidence shows they are associated with hoarseness, but their impact on vocal cord function has not been fully identified. Objectives. To describe the preliminary laryngeal findings in patients undergoing chemotherapy with VEGF/R inhibitors, and to describe possible mechanisms of their effect on vocal fold function. Methods. A retrospective case series was conducted in a tertiary medical center between July 2008 and August 2022. Cancer patients developing hoarseness while undergoing chemotherapy with VEGF/R inhibitors underwent videolaryngostroboscopy. Results. The study included four patients. There were three females and one male, treated for breast, lung, and unknown primary cancer, respectively. All 4 patients developed hoarseness 2–7 days after initiating treatment with the VEGF/R inhibitor drugs aflibercept (n = 1) and bevacizumab (n = 3). In all patients, videolaryngostroboscopy revealed vocal fold bowing and pronounced glottic insufficiency. There were no signs of mucositis or paralysis. In three patients, treatment involved speech therapy, with or without vocal fold augmentation. The average follow-up was 10 months (range 8–12 months). In 2 patients, there was a return of normal voice quality with resolution of vocal fold bowing. In one patient, who remained on chemotherapy, there was persistent bowing. Conclusions. VEGF/R inhibitors are associated with vocal fold bowing and glottic insufficiency. This appears to be a reversible side effect. To our knowledge, this is only the second clinical description of the effect of VEGF/R inhibitors on vocal fold function.